Three-dimensional magnetotelluric signatures and rheology of subducting continental crust: Insights from Sikkim Himalaya, India. (March 2023) - Konda, Shankar; Patro, Prasanta K.; Reddy, K. Chinna; Babu, Narendra
Abstract: 3D inversion of broad band MT data present variation of electrical signatures across the subducting Indian crust in Sikkim Himalaya. The vertical and horizontal geoelectric cross-sections are dominated by north-east dipping conductive zones. Two high conductivity zones (4–8 Ω m) at a depth of 5–18 km in Lesser Himalayan Domain (LHD) are explained by conductive mineral assemblage associated with abundant low saline and entrapped fluids. Another conductive feature (6–16 Ω m) in Main Himalayan Thrust Zone close to Main Himalayan Thrust ramp could have arisen from entrapment of CO2 -H2 O fluids and fluids released by metamorphic reactions. The high conductive anomaly (4–10 Ω m) at a depth of 5–16 km in Greater Himalayan Sequence (GHS) is caused by the presence of partial melts/aqueous fluids derived by present day fluid-absent melting of leucogranite source rocks. A combination of leucogranite intrusion, shear heating, and radiogenic heat production (4–17 μW/m 3 ) are the heat sources for inferred partial melting. Though, the constrained melt fractions of 1.4–3.8% in GHS are lower than the estimation in south Tibet that might be due to the less intrusion of leucogranites. The obtained moderate viscosities of (10 4.19 -10 5.49 Pa.s) from empirical relation with low melt and fluid fractions of 5–6 wt% in high conductive zone suggest viscous/ductile deformation and weakening mid-crust beneath northern Sikkim Himalaya. However, the estimated values of melt fractions and viscosities at mid-crustal depth of GHS are insufficient to develop a melt channel to flow southward between Main Central Thrust-1(MCT-1) and South Tibet Detachment (STD) envisaged by channel flow model. Highlights: 3D MT imaging of Sikkim Himalaya reveal lateral and transverse variation of crustal signatures. Conductivity anomaly beneath GHS may be due to presence of partial melt/aqueous fluids. The study suggests a change in mid-crustal rheology caused by moderate viscous deformation.